Study Influence of adding Surfactant to polymers in Reduce Friction in Pipelines - Hawege, Emsalem; Abushina, Almaki (Libyan Journal of Science &Technology, 2022)
When polymers (DRA) passes through high shear force areas like pumps and elbows that causes from turbulent flow will lose their drag reduction abilities. In this research, the effect of adding a nonionic surfactant (tween 20) to the cationic polymer (Poly (acrylamide-co-diallyl-dimemethylammonium chloride)) in reducing friction in the pipeline has been examined by using rotating disk apparatus to verify its ability in decrease the friction in pipelines. The influence of adding polymer, surfactant and Reynold number in enhancing flow in pipelines were examined. The results appeared that 40% drag reduction could be obtained by using this complex.